Quantifying the physical demands in netball to develop training guidelines that assess player preparation and reduce injury - McManus, Alexandra; Stevenson, M. (Sports Medicine Australia, 2007)
The risk of injury in sport is associated with the physical demands of the sport being played. It has been suggested that although participants may be fit and skillful, they may not be conditioned to meet the demands of their position. The aim of this study was to quantify the positional demands placed on players during games and to provide training guidelines to maximise performance and minimise injury. One team from the highest-level community competition in Western Australia was videotaped during pre-season training, and throughout the 2001 sporting season (43 player/hours), to determine the physical demands placed on participants. The centre typically performed the most movements (n=1012), followed by the wing (n=736), the shooter (n=663) and defence (n=636). The longest time spent in any one movement before changing to another was 11 seconds. All positional groups spent the majority of their game time walking, jogging or standing, however there were significant differences in each across positions. The greatest disparity between positional groups related to the time spent walking (range 38% to 54%), jogging (range 12% to 36%), standing (range 11% to 24%) and utility movements (range 3% to 11%). The distance travelled by players over a game ranges from 7 km (shooters) to 8.8km (centre) .The centre completed 50% more netball-specific activities (n=300) than any other position. Oneway ANOVA ‘s indicated there were significant differences between positional demands during games however, the training sessions observed did not appear to adequately prepare participants to meet these demands..The centre completed 50% more netball-specific activities (n=300) than any other position. Oneway ANOVA 's indicated there were significant differences between